Evolutions of Capitalism : Historical Perspectives, 1200-2000 - Rössner, Philipp Robinson; Casson, Catherine (Book collections on Project MUSE., 2022)
Covering times, places and topics that have often been overlooked in the existing economic history literature, this collection charts the most comprehensive chronology of capitalism to date.